OUTBREAK AND DAMAGE TO MONILIOSIS IN A DOUGHNUT PLANT - Suyunova Gulnora Begaliyevna (Web of Journals Publishing, 2024)
This article observed between 19.0 and 22.5% of flowers, flowers, leaves, branches, and 10.8 to 11.2% of the disease's development.
Keywords: Hawthorn moniliosis disease - (Monilia fructigena), Disease progression,Turkiston Karolkova, Pontika.